Reading with your hands. A review on haptic media studies - Arri, Francisco (InMediaciones de la Comunicación, 2019)
This article is a review of the existing literature regarding the origins and development of haptic studies in relation to new navigation practices by content proposed by the mobile communication ecosystem in terms of detachment and transformation of the materiality of the supports caused by reading on mobile devices or smartphones. In this way, the renewed forms of navigation have transformed the link between texts, readers and platforms. The perspective of haptic studies takes into consideration the transcendence of the tactile sense in the practice of daily reading. The objective of this article is to bring together the most important authors of this branch of study in order to establish a status of the issue within the framework of mobile communication.